Assessment of Knowledge and Attitude Towards Oral Health and Periodontal Disease in Diabetic Patients among Libyan Physicians - Elbarasi, Amelsaad; Mahfoud, Salma; Elzaidy, Nazeha (Libyan Journal of Dentistry, 2024)
Background: Periodontitis is a chronic inflammatory disease characterized by the destruction of the supporting structures of the teeth. Emerging research suggests a bidirectional link between diabetes mellitus (DM) and periodontal disease (PD). This indicates that DM elevates the risk of developing PD, while periodontal inflammation may contribute to increased blood sugar levels and worsen glycemic control. Aim: To determine the knowledge and attitude of internal medicine physicians towards oral health and periodontal disease in public and private diabetic clinics within the city of Benghazi, Libya. Methods: A cross-sectional study among practicing physicians who treat diabetic patients in various clinics within the city limits of Benghazi, Libya. A structured questionnaire consisting of 30 questions was utilized to assess the physicians’ demographics, their understanding of periodontal disease, and their attitudes towards the oral health of diabetic patients. Results: The study findings indicated that a positive attitude was more prevalent among female physicians (75%) than their male counterparts (25%). Conversely, a negative attitude was predominantly observed in senior house officers (93.8%), whereas consultants and physicians with over 10 years of experience demonstrated a positive attitude, accounting for 22.4% and 55.3% respectively. The data also revealed a statistically significant association between the attitude and knowledge level and the basic demographic characteristics of the participants, with a p-value < 0.05. Conclusion: Although most physicians are aware of the impact that PD and DM have on overall patient health, a knowledge deficiency is evident among senior house officers. In contrast, consultants possess the most comprehensive knowledge. The physicians also expressed a willingness to enhance their understanding of PD to improve health outcomes for their diabetic patients.